Delivery workers, trapped in an algorithmic system - Rani, Uma; Dhir, Rishabh Kumar; Gobel, Nora (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2022)
This article analyses the processes through which delivery workers are controlled by the algorithmic management practices on delivery platforms. The article builds on the existing literature on algorithmic management and control, by identifying the different types of control mechanisms used by platforms to discipline delivery workers in developing countries. It draws on surveys conducted by the International Labour Organization with about 3000 platform delivery workers in eleven developing countries (Argentina, Chile, China, Ghana, India, Indonesia, Kenya, Lebanon, Mexico, Morocco, and Ukraine) to understand how algorithmic management practices exert control and undermine workers’ freedoms at work. It discusses the implications of such a control mechanism on their working conditions, as well as their freedom and autonomy to undertake and perform work. The article concludes with a discussion on what policies have helped to address some of the issues related to working conditions and what policy measures need to be taken to ensure decent working conditions for workers on digital labour platforms.